Professional trader discipline and trade disposition - Locke, Peter R.; Mann, Steven C. (Journal of Financial Economics, 2005)
Recent evidence indicates irrational behavior among retail investors. They hold onto losses and sell winners in a manner consistent with the disposition effect. Market professionals often use the term “discipline” to indicate trading strategies that minimize potential behavioral influences. We investigate the nature of trading discipline and whether professional traders are able to avoid the costly irrational behaviors found in retail populations. The full-time traders in our sample hold onto losses significantly longer than gains, but we find no evidence of costs associated with this behavior. The successful floor futures traders in our sample exhibit trading behavior characterized as rational and disciplined. Moreover, measures of relative trading discipline have predictive power for subsequent trading success.